2019
DOI: 10.31983/manr.v1i2.5287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baby Massage on Baby Weight Aged 0-6 Months

Abstract: Background : Infancy is a golden period as well as a critical period of development. It is said to be a critical period because at this time the baby is very sensitive to the environment and is said to be a golden period because the time is very short and cannot be repeated again. Stimulation in infancy is very necessary to stimulate growth and development. Baby massage is an activity carried out by parents or caregivers of the baby as an act of stimulating the growth and development of the baby Purpose : The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This research is also in accordance with several previous studies that stated that baby massages performed on small-weight babies, whether pre-term babies or babies with a body weight below standard, can increase body weight (Fatmawati et al, 2021;. Previous research has not produced findings on how often massage is given to babies, which can increase body weight (Fatmawati et al, 2021;Hasanah et al, 2019;Sutarmi et al, 2022). Meanwhile, in this current study, it was found that weight gain began to occur in the second week of the baby massage process, and there was an increase every week from the baby massage process.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This research is also in accordance with several previous studies that stated that baby massages performed on small-weight babies, whether pre-term babies or babies with a body weight below standard, can increase body weight (Fatmawati et al, 2021;. Previous research has not produced findings on how often massage is given to babies, which can increase body weight (Fatmawati et al, 2021;Hasanah et al, 2019;Sutarmi et al, 2022). Meanwhile, in this current study, it was found that weight gain began to occur in the second week of the baby massage process, and there was an increase every week from the baby massage process.…”
Section: Discussionsupporting
confidence: 91%
“…There are many factors that cause stunting in Indonesia, including the fact that babies are still found to be underweight and do not receive enough stimulation, resulting in babies who are thin and malnourished (WHO, 2018). To overcome stunting, many programs have been created and developed by the government, including providing supplementation during the antenatal period, monitoring and providing exclusive breastfeeding to babies (Hasanah et al, 2019;Munira, 2023). Monitoring baby growth and development provides good results by detecting early the possible risk of stunting in babies (Taqwin et al, 2022a), so that interventions can be carried out to prevent the risk of stunting (Ishikawa & Shiga, 2012).…”
Section: Introductionmentioning
confidence: 99%